The Impact of Environmental, Social, Governance, and Innovation Factors on the Sustainable Competitiveness of Chinese Private Universities - Junli Wang; Abu Bakar Bin Abdul Hamid (International Journal of Social Sciences and Public Administration, 2026)
This study takes private universities in Xi’an, China, as the research object and explores how environmental, social, and governance factors, together with innovation capability, influence the sustainable competitiveness of private universities through brand building. Based on the Resource-Based View, Stakeholder Theory, Dynamic Capability Theory, and Brand Equity Theory, this study constructs a theoretical model linking environmental, social, governance, and innovation capability with brand image, brand competitiveness, and sustainable competitiveness. A quantitative research method was adopted, and data were collected through a questionnaire survey. A total of 550 questionnaires were distributed, of which 527 valid responses were obtained. Descriptive statistics, reliability and validity tests, exploratory factor analysis, confirmatory factor analysis, structural equation modeling, and mediation effect analysis were employed for empirical testing. The results indicate that environmental, social, and governance factors have positive effects on brand image, while innovation capability significantly promotes brand competitiveness. In addition, brand image and brand competitiveness positively affect the sustainable competitiveness of private universities. Brand building plays a crucial mediating role between environmental, social, governance, innovation capability, and sustainable competitiveness. The findings suggest that, in order to enhance long-term competitive advantages, private universities should integrate green development, social responsibility, governance optimization, and innovation-driven development into their brand strategies. This study not only enriches the theoretical perspectives on brand building and sustainable competitiveness in private universities, but also provides practical implications for the high-quality and sustainable development of private universities in China.